Understanding Technology Adoption from the “Multiple Cultures Perspective”: The Case of a Successful Post-Implementation Recovery - Beeler, Betty; Saint-Léger, Guy (Management international / International Management / Gestiòn Internacional, 2014)
The purpose of this article is to explore the pertinence of the “multiple cultures perspective” in the context of technology adoption. Proponents of this perspective assert that people are shaped by diverse and sometimes conflicting values, any of which will be more salient than others in a given context. We show how the changing salience of some end-users’ values helped salvage a disastrous ERP project at a French auto parts company. Our findings show how a less deterministic vision of cultural resistance to ERP systems can help organizations achieve their objectives.